Effects of elevated CO2 concentration and increased temperature on leaf quality responses of rare and endangered plants - Jeong, Heon-Mo; Kim, Hae-Ran; Hong, Seungbum; You, Young-Han (Journal of ecology and environment, 2018)
Background In the study, the effects of elevated CO 2 and temperature on the nitrogen content, carbon content, and C:N ratio of seven rare and endangered species ( Quercus gilva , Hibiscus hambo , Paliurus ramosissimus , Cicuta virosa , Bupleurum latissimum , Viola raddeana , and Iris dichotoma ) were examined under control (ambient CO 2 + ambient temperature) and treatment (elevated CO 2 + elevated temperature) for 3 years (May 2008 and June 2011). Results Elevated CO 2 concentration and temperature result in a decline in leaf nitrogen content for three woody species in May 2009 and June 2011, while four herb species showed different responses to each other. The nitrogen content of B. latissimum and I. dichotoma decreased under treatment in either 2009 and 2011. The leaf nitrogen content of C. virosa and V. raddeana was not significantly affected by elevated CO 2 and temperature in 2009, but that of C. virosa increased and that V. raddeana decreased under the treatment in 2011. In 2009, it was found that there was no difference in carbon content in the leaves of the six species except for that of P. ramosissimus . On the other hand, while there was no difference in carbon content in the leaves of Q. gilva in the control and treatment in 2011, carbon content in the leaves of the remaining six species increased due to the rise of CO 2 concentration and temperature. The C:N ratio in the leaf of C. virosa grown in the treatment was lower in both 2009 and 2011 than that in the control. The C:N ratio in the leaf of V. raddeana decreased by 16.4% from the previous year, but increased by 28.9% in 2011. For the other five species, C:N ratios increased both in 2009 and 2011. In 2009 and 2011, chlorophyll contents in the leaves of Q. gilva and H. hamabo were higher in the treatment than those in the control. In the case of P. ramosissimus , the ratio was higher in the treatment than that in the control in 2009, but in 2011, the result was the opposite. Among four herb species, the chlorophyll contents in the leaves of C. virosa , V. raddeana , and I. dichotoma did not show any difference between gradients in 2009, but decreased due to the rise of CO 2 concentration and temperature in 2011. Leaf nitrogen and carbon contents, C:N ratio, and chlorophyll contents in the leaves of seven rare and endangered species of plant were found to be influenced by the rise and duration of CO 2 concentration and temperature, species, and interaction among those factors. Conclusions The findings above seem to show that long-term rise of CO 2 concentration, and temperature causes changes in physiological responses of rare and endangered species of plant and the responses may be species-specific. In particular, woody species seem to be more sensitive to the rise of CO 2 concentration and temperature than herb species.